A media for diversity : LGBT in the news - a guide for better reporting - Sjöding, Anette; Laurell, Thomas; Platovas, Eduardas (Vilnius : Lithuanian Gay League, 2008)
Fonds Suzan Daniel (FSD)
Engels
Monografie